The Role of Russian Multinational Companies: toward Maturity - Andreff, Wladimir (Papeles de Europa, 2011)
The study of Russian multinational companies (MNCs) becomes a true field of research covered by a hundred of publications. In the first place the conditions of the origination of these companies are evoked, in the second one the comparison of their foreign investment toward the other countries in transition is being run; afterwards their industrial and regional specificity is empirically exposed. Russian MNCs can be difficult to suit the framework of the existing theories due to the fact of their opacity and their interrelations with the Russian State policy, which demands the elaboration of the particular explanation model. Apart from these last considerations, it is important to highlight that Russian MNCs became one of the mainstays of the State capitalism in Russia.
Keywords: Multinational companies (MNCs); Russia; Foreign Direct Investment (FDI); State capitalism